2018
DOI: 10.5194/acp-18-3299-2018
|View full text |Cite
|
Sign up to set email alerts
|

Non-methane organic gas emissions from biomass burning: identification, quantification, and emission factors from PTR-ToF during the FIREX 2016 laboratory experiment

Abstract: Abstract. Volatile and intermediate-volatility non-methane organic gases (NMOGs) released from biomass burning were measured during laboratory-simulated wildfires by protontransfer-reaction time-of-flight mass spectrometry (PTRToF). We identified NMOG contributors to more than 150 PTR ion masses using gas chromatography (GC) preseparation with electron ionization, H 3 O + chemical ionization, and NO + chemical ionization, an extensive literature review, and time series correlation, providing higher certainty f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
543
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 288 publications
(582 citation statements)
references
References 63 publications
33
543
6
Order By: Relevance
“…In general, biomass burning, which includes wildfires, is the main global source of fine carbonaceous aerosol particles (~75%) in the atmosphere (Andreae and Merlet, 2001;Bond and Bergstrom, 2006;IPCC, 2014;Park et al, 2007). Individual and categorized organic emissions from wildfires have previously been 15 identified and quantified (Akagi et al, 2011;Andreae and Merlet, 2001;Hatch et al, 2015;Kim et al, 2013;Koss et al, 2018;Liu et al, 2017;Mazzoleni et al, 2007;Naeher et al, 2007;Oros et al, 2006;Oros and Simoneit, 2001a;Simoneit, 2002;Stockwell et al, 2015;Yokelson et al, 2013). The bulk of previous studies on speciated organic compound emissions focused on gas-phase volatile organic compounds (VOCs).…”
Section: Introductionmentioning
confidence: 99%
“…In general, biomass burning, which includes wildfires, is the main global source of fine carbonaceous aerosol particles (~75%) in the atmosphere (Andreae and Merlet, 2001;Bond and Bergstrom, 2006;IPCC, 2014;Park et al, 2007). Individual and categorized organic emissions from wildfires have previously been 15 identified and quantified (Akagi et al, 2011;Andreae and Merlet, 2001;Hatch et al, 2015;Kim et al, 2013;Koss et al, 2018;Liu et al, 2017;Mazzoleni et al, 2007;Naeher et al, 2007;Oros et al, 2006;Oros and Simoneit, 2001a;Simoneit, 2002;Stockwell et al, 2015;Yokelson et al, 2013). The bulk of previous studies on speciated organic compound emissions focused on gas-phase volatile organic compounds (VOCs).…”
Section: Introductionmentioning
confidence: 99%
“…The PTR-ToF was used to measure VOCs with a proton affinity greater than that of water, including formaldehyde, 2,3-butanedione, 2,3-pentanedione, and several other carbonyl species, with a time resolution of 1 Hz (Yuan et al, 2016;Koss et al, 2018). For some species, such as formaldehyde and acetaldehyde, calibration factors were determined via the addition 25 of standards, but for other compounds such as 2,3-butanedione the calibration factors were calculated using the method of Sekimoto et al (2017).…”
Section: Ptr-tofmentioning
confidence: 99%
“…8, and at these methylglyoxal concentrations the small features can be resolved, indicating that at least part of the signal attributed to methylglyoxal is indeed from that molecule. However, previous work has shown that the other substituted α-dicarbonyls are emitted from biomass burning in amounts comparable to the 25 methylglyoxal emissions we measured at the FSL (Gilman et al, 2015;Stockwell et al, 2015;Koss et al, 2018), and the contribution of these species to the measured extinction needs to be taken into account to properly retrieve the methylglyoxal concentrations.…”
mentioning
confidence: 99%
See 2 more Smart Citations